In utero: an account of six cases observed and treated in dispensary practice - Thomson, W. M. (The University of Edinburgh, 1940)
[Hand-written]
In utero: an account of six cases observed and treated in dispensary practice: written for the Sir Humphry Rolleston Prize, 1940